Review of the genus Bythonia Oman 1936 with description of a new species and new record from Venezuela (Hemiptera, Cicadellidae, Iassinae) - Gaiani, Marco A. (Zootaxa, 2017)
Bythonia freytagi sp. nov. is diagnosed and described from northern Venezuela. Bythonia rugosa is recorded for the first time in Venezuela from the southern state of Amazonas. The presence of both species of Bythonia in Venezuela represent the first occurrences of this genus north of the Equator. Comments on the relationships of the described species are made and two species groups are proposed. A checklist and key to the known species of the genus are provided.